Antibody - fusion proteins anti-CD22 recombinant immunotoxin Moxetumomab Pasudotox - Kreitman, Robert J. (2011)
Recombinant immunotoxins are fusion proteins containing the cytotoxic portion of a protein toxin fused to the Fv portion of an antibody. The Fv binds to an antigen on a target cell and brings the toxin into the cell interior, where it arrests protein synthesis and initiates the apoptotic cascade. Moxetumomab pasudotox, previously called HA22 or CAT-8015, is a recombinant immunotoxin composed of the Fv fragment of an anti-CD22 monoclonal antibody fused to a 38 kDa fragment of Pseudomonas exotoxin A, called PE38. Moxetumomab pasudotox is an improved more active form of a predecessor recombinant immunotoxin BL22 (also called CAT-3888), which produced complete remissions (CRs) in relapsed/refractory hairy cell leukemia (HCL), but had < 20% response rate in chronic lymphocytic leukemia (CLL) and acute lymphoblastic leukemia (ALL), diseases in which the leukemic cells contain much lower numbers of CD22 target sites. Compared to BL22, moxetumomab pasudotox is up to 50-fold more active on lymphoma cell lines and leukemic cells from patients with CLL and HCL. A phase I trial was recently completed in HCL patients, who achieved similar response rates as BL22 but without dose-limiting toxicity. Besides additional testing in HCL, moxetumomab pasudotox is being evaluated in phase I trials in patients with CLL, B-cell lymphomas, and childhood acute lymphoblastic leukemia. Moreover, protein engineering has been used to increase its activity and to decrease non-specific side effects and remove B cell epitopes.